Marketing Incentive Programs and Sales Performance of Pioneer Adhesive Inc. – Basis for Action Plan - Bernal, David (International Journal of Research in Interdisciplinary Studies, 2025)
Marketing Incentive programs have emerged as a strategic tool for businesses seeking to drive sales growth, foster customer loyalty, and enhance brand perception. This study synthesizes existing research to highlight the significance of participant engagement, cost effectiveness, customer loyalty, and positive customer experience in incentive marketing. The findings underscore the importance of personalization, transparency, and simplicity in incentive program design, demonstrating that businesses that adopt data-driven, personalized, and user-friendly incentive strategies can expect significant improvements in customer retention, sales performance, and brand advocacy. The study reveals that well-designed incentive programs can increase customer retention rates by 5-20%, drive sales growth of 10-30%, and enhance customer satisfaction and loyalty. By optimizing incentive programs, businesses can unlock sustainable growth, cultivate long-term customer relationships, and gain a competitive edge in the market. The findings provide valuable insights for businesses seeking to leverage incentive marketing as a strategic growth driver.